STRATEGI KEBERLANJUTAN USAHA PERCETAKAN CV DEALIMA PROSENT - Robi’atul Adawiyah Bukhori; Vembri Aulia Rahmi (CV. Denasya Smart Publisher, 2025)
The main focus of this study is on the implementation of sustainability strategies and dynamic capabilities, This study aims to identify and analyze factors that influence business sustainability at CV. Dealima Prosent, Through a qualitative approach with a phenomenological method This research was conducted at CV. Dealima Prosent which is located in Dusun Gantang, Boboh Village RT 03 RW 02, Menganti District, Gresik Regency, the study was conducted for 3 months. Data collection techniques with observation, interviews and documentation. The results of the study indicate that the sustainability of CV. Dealima Prosent's business is greatly influenced by the management of skilled and competent human resources, as well as the application of the latest technology to improve efficiency and product quality, to further strengthen competitiveness, companies are recommended to expand non-technical training for employees, develop an online platform for customer service, and highlight quality and service to compete in the market. The research subjects involved 1 business owner, 1 employee and 4 Customers. Data validity testing using triangulation, namely sources, data collection techniques, and time. This study explores an in-depth understanding of the challenges faced by companies in maintaining competitiveness in the increasingly competitive printing industry. In terms of theory, it is suggested that future research develop a Dynamic Capability framework that is more relevant to SMEs, by including the dimension of customer participation in sensing (customer-driven sensing) and adding focus on organizational culture transformation and local value-based learning. In addition, integrating the concept of business resilience into this theory is very important to deal with uncertainty and crisis. The development of this theory will be increasingly applicable to SMEs in building an adaptive and inclusive business sustainability model.